Comparison of Different Clinical and Metabolic Parameters Among Type 2 Diabetic Patients With and Without Retinopathy in Primary Health Clinics in Medan City, North Sumatera, Indonesia (Bangladesh Journal of Medicine, 2020)
Background: The global prevalence of type 2 diabetes mellitus is increasing steadily and diabeticretinopathy is one of the microvascular complications of diabetes mellitus. This research aims tocompare different clinical and metabolic parameters among type 2 diabetic patients with and withoutdiabetic retinopathy.Methods: This cross-sectional study was done at various primary health care centers in Medan cityand the surrounding areas in North Sumatera from May to July 2020. Collected medical data includedblood pressure, body mass index, duration of disease, family history and medical treatment. Laboratorydata included blood glucose, glycated hemoglobin (HbA1c) and lipid profile. Diabetic retinopathy wasdetected by funduscopic examination by an ophthalmologist.Results: Total patients were 88 and 26 had retinopathy. There was significant difference betweenthe average blood pressure, blood glucose and HbA1C values among patients with type 2 diabetesmellitus with and without retinopathy (p